Experimental investigation of synthesis gas production in fuel-rich oxy-fuel methane flames. (1st June 2022) - Sentko, M.M.; Schulz, S.; Weis, C.; Stelzner, B.; Anderlohr, C.; Vicari, M.; Trimis, D.
Highlights: Measured concentration profiles of fuel-rich CH4 /O2 -flames using a GC/MS. Profile-shift (up to 1.4 mm) caused by the probe determined from detailed CFD. Syngas production (H2 /CO2 and CO/H2 O ratio) depends essentially on mechanism used. Detailed analysis of two mechanisms to identify differences in major products. C2 H2 decomposition is better reproduced by CalTech2.3 due to detailed Cx chemistry. Abstract: Combustion processes with pure oxygen (oxy-fuel) instead of air as an oxidant are attractive for e.g. high temperature thermal or thermochemical and gasification processes. The absence of nitrogen as an inert gas leads in such combustion processes to an increase in temperature and species concentrations. The scope of this study is the determination of axial profiles of major educts (CH4, O2 ) and major combustion products such as H2, H2 O, CO and CO2 in flat fuel-rich premixed methane-oxygen flames (2.5 ≤ ϕ <3.0). A Heat-Flux-burner was used to stabilize a quasi-adiabatic one-dimensional flame at a preheating temperature of TP  = 300 K and atmospheric pressure. Gas samples were taken at different HAB using a quartz probe and analyzed by a GC/MSD. The influence of the probe on determined species concentrations was investigated using CFD simulations. Additionally, one-dimensional calculations with detailed chemistry were performed using the GRI3.0 and CalTec2.3 mechanism. Their differences in regards to H2, H2 O and CO concentrations were thoroughly investigated and could be explained by the detailed C2 -chemistry of the CalTech2.3. The results of the analyzed gas samples show a rapid reduction and increase in the flame zone, of the educts, major products and higher hydrocarbons (C2 H2, C2 H4 and C6 H6 ), respectively. Both mechanisms show a sharper gradient of the synthesis gas production in comparison to the experimental results, nevertheless a tendency towards the CalTech2.3 scheme is observed. In the post flame zone the determined species concentrations of H2 and CO2 correspond to the results of the GRI3.0, whereas in the case of H2 O and CO the CalTech2.3 showed better performance. The calculations of higher hydrocarbons are in better agreement with higher equivalence ratio.